Parents' Beliefs and Behaviors About Their Children's Literacy Development: A Cross-Sectional Study in Saudi Arabia - AlAhmari, Fatimah Saeed (Frontiers in Pediatrics, 2022)
Background: A home environment that promotes learning is a meaningful factor in school performance in which children’s parents are involved in their education. However, little research has focused on parents’ reading-related beliefs or the relationship between parents’ literacy beliefs and behaviors. Method: This cross-sectional study describes the range of parents’ reported literacy beliefs and behaviors and examines whether an association exists among them Saudi Arabia. It was conducted on a convenient sample of 100 parents using a web-based self-administrated shared with families in developmental and Behavioural Paediatrics clinics at multiple sites utilizing the Parents’ Perceptions of Literacy Learning Interview Schedule (PPLLIS). Results: There were 83 mothers and 17 fathers, 90% had a university degree and higher. Parents’ beliefs ranged between 87 and 123, with a mean of 103.54±8.05, indicating more holistic perceptions than skills-based ones. There was only a positive significant correlation between parents’ beliefs and behaviors regarding their participation in literacy activities where those participating in literacy activities with their kids were parents with more holistic and who scored in the top one-third on the PPLLIS. Conclusion: Parents’ beliefs and their reported behaviors are found to be significantly impacted by their educational levels. Future investigations and national campaigns are encouraged to improve the educational levels of parents, especially in urban areas.